Challenges in sedation and analgesia management in the critically ill patients: A survey study - Shrestha, Samichhya; Magar, Rita; Thapa, Karuna; Gautam, Prabha; Rimal, Ankit; Paneru, Hem Raj (Journal of Nepalese Society of Critical Care Medicine, 2025)
Background and aims: Sedation and analgesia management in critically ill patients is vital to reduce incidents, ICU stay, costs, morbidity, and mortality. Achieving optimal sedation is challenging due to patient variability, dynamic clinical situations, and unknown barriers to protocol implementation. This study aims to identify the barriers in ICU sedation and analgesia management.Methods: This prospective observational survey study included 94 nurses working in the Intensive Care Unit (ICU) of Tribhuvan University Teaching Hospital (TUTH) between December 30, 2022, and January 30, 2023. Data were collected using a semi-structured questionnaire.Results: Major barriers to sedation management included fear of over sedation, adverse events, hemodynamic instability, and increased staff workload. For analgesia, barriers included concerns about drug dependence and prescription delays. Setting Richmond Agitation Sedation Scale (RASS) targets helped sedation management, while ongoing education was least helpful for sedation and analgesia.Conclusions: This study identifies key challenges in sedation and analgesia management for critically ill patients, including fears of over sedation, lack of protocols, insufficient training, and heavy workloads. While RASS assessment was a helpful facilitator, ongoing education was less effective. Implementing structured protocols, continuous training, and better collaboration is essential to improve care.